2020
DOI: 10.3390/pharmaceutics12090845
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanoparticles for Enhancing the Physicochemical Stability and Topical Skin Delivery of Orobol

Abstract: Orobol is one of the major soy isoflavones, and has been reported to have various pharmacological activities, including an anti-skin-aging effect. However, since it has low solubility in water and physicochemical instability, the formulation of orobol for delivery into the dermal layer of the skin could be challenging. The objective of this study was to prepare lipid nanoparticles formulations of orobol to enhance its stability as well as its deposition into the skin. Formulations of orobol-loaded solid lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
(53 reference statements)
0
21
0
Order By: Relevance
“…For these reasons, many researchers are searching for new phytochemicals with use as topical formulations to increase their stability and delivery efficiency. [30][31][32][33][34] In this study, for the first time, we found a metabolite of genistein, orobol, which has anti-atopic effects in animals and cell models.…”
Section: Discussionmentioning
confidence: 89%
“…For these reasons, many researchers are searching for new phytochemicals with use as topical formulations to increase their stability and delivery efficiency. [30][31][32][33][34] In this study, for the first time, we found a metabolite of genistein, orobol, which has anti-atopic effects in animals and cell models.…”
Section: Discussionmentioning
confidence: 89%
“…Polymeric micelles Curcumin Whitening [183] Nanostructured lipid carriers Passiflora edulis seeds oil Whitening [184] Niosomes Quercetin Whitening [109] Niosomes Arbutin Whitening [110] Nano sponges Azelaic acid Whitening [145] Nanostructured lipid carriers Orobol Anti-ageing [185] Nanoliposomes Carnosine Palmitoyl tripeptide-5 Acetyl hexapeptide-3 Anti-ageing [186] Table 3. Cont.…”
Section: Nanocarriers Active Ingredients Cosmetic Use Referencesmentioning
confidence: 99%
“…These lipids including soybean oil, coconut oil, sesame oil, linseed oil, and grape seed oil are already verified to be biodegradable and biocompatible. The topically applied NLCs are reported to be safe to cause no skin irritation in human [170]. The lipid nanoparticles made with linseed oil is safe for skin application because the nanoparticles were not irritant, sensitizing, and comedogenic on skin [171].…”
Section: The Safety Of Nanoparticles On Skinmentioning
confidence: 99%